Influence of productivity and processing method on physicochemical characteristics of white button mushrooms in Brazil - Zied, Diego Cunha; Penachio, Sara Maciel [UNESP]; Dias, Eustáquio Souza; Minhoni, Marli Teixeira de Almeida [UNESP]; Ferraz, Rafael Augusto [UNESP]; Vieites, Rogério Lopes [UNESP] (Wiley, 2014)
Background: The white button mushroom is the edible fungus most commonly cultivated and commercialized in Brazil and worldwide. This work assesses the productivity of the different strains ABI 07/06 and ABI 06/05 of Agaricus bisporus grown under the conditions normally employed by growers in the southeast of Brazil, and the influence of four different chemical conservation methods on the physicochemical characteristics and storage properties of the fruit bodies. Rresults: The productivities of strains ABI 07/06 and ABI 06/05 of white button mushrooms were found to be comparable. The colorimetric characteristics and chemical compositions (fat, fiber and protein contents) of the mushroom strains were similar, and these parameters were not influenced significantly by the conservation processes. Texture was negatively affected by all processing methods employed. Conclusion: It was concluded that chemical methods of processing mushrooms were not fully effective and novel alternative technologies should be considered by mushroom processors in Brazil. Some methods of mushroom storage using chemicals such as sodium metabisulfite are harmful to the human organism, so processing using autoclaving may be the best form of conservation of canned mushrooms.
Keywords: Agaricus bisporus; Postharvest processing; Physicochemical characteristics; Storage properties